Effects of Steel Cell Components on Overall Capacity of Pulsed Laser Deposited FeF2 Thin Film Lithium Ion Batteries. Issue 8 (6th June 2015) - Khateeb, Shadi Al; Lind, Aaron G.; Santos-Ortiz, Reinaldo; Shepherd, Nigel D.; Jones, K. S.
Abstract : 130 nm FeF2 films were deposited on AISI 304 steel substrates by pulsed laser deposition for use as cathodes in lithium ion batteries (LIBs). Aluminum and steel leads pouch cells as well as coin cell battery configurations were used to determine the effect of cell materials on galvanostatic and cyclic voltammetry tests. It was observed that there is a large increase in measured capacity for FeF2 films cycled using pouch cells with steel leads relative to pouch cells using aluminum leads. Transmission electron microscope (TEM) imaging showed similar microstructural behavior of the cycled FeF2 films irrespective of the use of steel leads or aluminum leads. Results of X-ray photoelectron spectroscopy and galvanostatic testing on bare stainless steel substrates suggest that the increase in capacity for cell configurations using steel components is due to the cycling of surface iron oxides and this can be avoided through the use of Al leads.